Diagnosis Of Cancer Of The Women In The Content Using Bayes Theorem - Syaifuddin, Muhammad (Ali Institute or Research and Publication, 2022)
Uterine cancer is a malignant process an event that occurs in female reproduction, so that the surrounding tissue cannot perform its function properly. This condition is usually accompanied by abnormal vaginal bleeding and discharge, this disease can occur repeatedly. The possibility of uterine cancer can attack the womb for pregnant women as great as those who are not pregnant. The condition of cancer in the uterus or reproduction during pregnancy is not something that is taken lightly so that it is immediately possible to take appropriate action and treatment. For proper treatment, of course, requires an expert who in this case is a doctor. However, it is not uncommon to get service and treatment from a doctor, having to wait a long time. This is because there are few doctors who handle this case but there are many patients who must be treated. This is not to mention the costs incurred are fairly large. With a fairly large cost, it is not uncommon for people to choose traditional medicine. Therefore, to overcome difficult problems and the high cost of treatment, one alternative is to provide an application to diagnose uterine cancer. With an application that can be accessed online, it makes it easier for the public to find out early on and seek treatment. The results of research that adopts an expert system and Bayes' theorem as an alternative are difficult and expensive to treat, so that people are more helped and get education from an early age.